How to counter organisational inertia to enable knowledge management practices adoption in public sector organisations. Issue 9 (24th March 2021) - Ashok, Mona; Al Badi Al Dhaheri, Mouza Saeed Mohammed; Madan, Rohit; Dzandu, Michael D.
Abstract : Purpose: Knowledge management (KM) is associated with higher performance and innovative culture; KM can help the public sector to be fiscally lean and meet diverse stakeholders' needs. However, hierarchical structures, bureaucratic culture and rigid processes inhibit KM adoption and generate inertia. This study aims to explore the nature and causes of this inertia within the context of the United Arab Emirates (UAE) public sector. Design/methodology/approach: Using an in-depth case study of a UAE public sector organisation, this study explores how organisational inertia can be countered to enable KM adoption. Semi-structured interviews are conducted with 17 top- and middle-level managers from operational, management and strategic levels. Interview data is triangulated with content analysis from multiple sources, including the UAE Government and case organisation documents. Findings: The results show transformation leadership, external factors and organisational culture mediate the negative effect of inertia on KM practices adoption. We find that information technology plays a key role in enabling knowledge creation, access, adoption and sharing. Furthermore, we uncover a virtuous cycle between organisational culture and KM practices adoption in the public sector. In addition, we develop a new model (the relationship between KM practices, organisational inertia, organisational culture, transformational leadership traits and external factors) and four propositions for empirical testing by future researchers. We also present a cross-case comparison of our results with six private/quasi-private sector cases who have implemented KM practices. Research limitations/implications: Qualitative data is collected from a single case study. Originality/value: Inertia in a public section is a result of bureaucracy and authority bounded by the rules and regulations. Adopting a qualitative methodology and case study method, the research explores the phenomena of how inertia impacts KM adoption in public sector environments. Our findings reveal the underlying mechanisms of how internal and external organisational factors impact inertia. Internally, supportive organisational culture and transformational leadership traits positively effect KM adoption, which, in turn, has a positive effect on organisational culture to counter organisational inertia. Externally, a progressive national culture, strategy and policy can support a knowledge-based organisation that embraces change. This study develops a new model (interactions between internal and external factors impacting KM practices in the public sector), four propositions and a new two-stage process model for KM adoption in the public sector. We present a case-comparison of how the constructs interact in a public sector as compared to six private/quasi-private sector cases from the literature.